SYSTEMATIC ANALYSIS OF THE QUALITY OF SELECTION AND EDUCATION OF GIFTED STUDENTS IN HIGHER EDUCATIONAL INSTITUTIONS (Proceedings of International Conference on Educational Discoveries and Humanities, 2023)
This article is devoted to the issues of selection and organization of training of gifted students, one of the main problems of the higher educational institution, and analyzes scientific research and advanced pedagogical experience on the study of talent in students.